QUALITY OF YOGURT BLENDED WITH THYMUS KOTSCHYANUS ESSENTIAL OIL - Mahmoudi, Razzagh; Gajarbeygi, Payman; Mahmodzadeh, Foad; Hassanzadeh, Mohsen; Kiyani, Raziyeh; Nadari, Mohammad Reza Asadi (Malaysian Journal of Science, 2014)
In agreement with the current trend of giving value to natural and renewable resources, the use of natural antimicrobial compounds, particularly in food and biomedical applications, becomes very frequent. The behaviour of Listeria monocytogenes during the cold storage (10 days) of yoghurt which was produced with Thymus Kotschyanus essential oil (0, 50, 150 and 300 ppm EO) with sensory attributes of yoghurt were investigated, in addition, The viability of starter culture bacteria were studied. Viable counts of L. monocytogenes fall was sharp from 3.00 to 1.07 (log cfu/g) at the first day and was not present at the other storage day in yoghurt with 300 ppm EO. In spite of L. monocytogenes could be isolated and counted in days 7 from control sample (1.19 log cfu/g). Yoghurt made with 150 ppm of the EO had the highest starter culture bacteria count at the end of storage. Considering the organoleptic effect of the EO, the best treatment with acceptable flavor, good appearance was obtained at 50 ppm EO. In conclusion, the combination of T. Kotschyanus EO treatment and other natural preservative was significantly effective in the inactivation of foodborne pathogens while maintaining acceptable yoghurt quality. Keywords: Yoghurt, Thymus kotschyanus EO, Listeria monocytogenes